2013
DOI: 10.1371/journal.pgen.1003204
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Ptf1a Induces Spinal Defects, Urogenital Defects, and Anorectal Malformations in Danforth's Short Tail Mice

Abstract: Danforth's short tail (Sd) is a semidominant mutation on mouse chromosome 2, characterized by spinal defects, urogenital defects, and anorectal malformations. However, the gene responsible for the Sd phenotype was unknown. In this study, we identified the molecular basis of the Sd mutation. By positional cloning, we identified the insertion of an early transposon in the Sd candidate locus approximately 12-kb upstream of Ptf1a. We found that insertion of the transposon caused overexpression of three neighboring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 56 publications
0
24
3
Order By: Relevance
“…As a consequence and contrary to wildtype littermates, Sd mice showed ectopic Ptf1a expression in the notochord and hindgut at E8.5 to E9.5, which extended to the cloaca and mesonephros at E10.5 and to the pancreatic bud at E10.5 and E11.5 [46]. The resultant phenotype of this Sd mutation not only causes reduction or absence of kidneys, but mirrors the complete phenotype of the human VATER/VACTERL association.…”
Section: Genetically Engineered Vater/vacterl Murine Mutant Models Wimentioning
confidence: 99%
“…As a consequence and contrary to wildtype littermates, Sd mice showed ectopic Ptf1a expression in the notochord and hindgut at E8.5 to E9.5, which extended to the cloaca and mesonephros at E10.5 and to the pancreatic bud at E10.5 and E11.5 [46]. The resultant phenotype of this Sd mutation not only causes reduction or absence of kidneys, but mirrors the complete phenotype of the human VATER/VACTERL association.…”
Section: Genetically Engineered Vater/vacterl Murine Mutant Models Wimentioning
confidence: 99%
“…Furthermore, recent reports have suggested that KRAB-ZFP gene content is distinct in different strains of laboratory mice (37,38), and reduced KRAB-ZFP gene content could contribute to increased activity in individual mice. Although we have yet to find obvious phenotypes in the mice carrying new insertions, novel ETn germ line insertions have been shown to cause phenotypes from short tails (39)(40)(41) to limb malformation (3) and severe morphogenetic defects including polypodia (42) depending upon their insertion site.…”
Section: Discussionmentioning
confidence: 99%
“…Exploded view shows the completely sequenced region, the ETn (red triangle) as the only variant in Sd . (F) Semba et al [7] demonstrate both the functional significance of the ETn and the requirement for a Ptf1a open reading frame using serial gene targeting of wild type–and Sd /+-derived ES cells and conventional transgenic mice. Blue triangles, variant loxP sites; red triangles, ETn insertion; colored boxes, neo (green), Ptf1a (deep purple), and Gm13336 (light purple) replacement cassettes.…”
mentioning
confidence: 99%
“…In this issue of PLOS Genetics , three laboratories independently identify the Sd mutation as an 8.5 kb ETn retrotransposon insertion 12.3 kb upstream from the Ptf1a gene [5][7]. Ptf1a encodes a cell type–restricted basic helix-loop-helix transcription factor required for development of the pancreas and cerebellum [8][10].…”
mentioning
confidence: 99%
See 1 more Smart Citation